A Forward-Backward SDEs Approach to Pricing in Carbon Markets - Chassagneux,J-F; Chotai,H; Muûls,M (Springer, 2017)
In this chapter, we consider a model for the valuation of carbon emissions market allowances. In each year from 2006 to 2011 inclusive, combustion installations accounted for between 72 and 75% of verified emissions under the EU ETS (Emissions Trading System), see Fig. 3.1. It is reasonable to assume that most of these installations are involved in electricity generation. Given the importance of power producers in such markets, the model focuses on the electricity generation sector.